1990
DOI: 10.1126/science.11538082
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Far-IRLaser Spectroscopy of Jet-Cooled Carbon Clusters: the ν 2 Bending Vibration of C 3

Abstract: Seven rovibrational transitions of the (01(1)0) <-- (00(0)0) fundamental bending band of C3 have been measured with high precision with the use of a tunable far-infrared laser spectrometer. The C3 molecules were produced by laser vaporization of a graphite rod and cooled in a supersonic expansion. The astrophysically important nu 2 fundamental frequency is determined to be 63.416529(40) cm-1. These measurements provide the basis for studies of C3 in the interstellar medium with far-infrared astronomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
67
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(71 citation statements)
references
References 15 publications
4
67
0
Order By: Relevance
“…If, however, the dispersion of 13 C is nonstatistical, then the experiment is inconclusive. A nonstatistical result is interprétable as either a large-molecule formation mechanism or as an indicator that the gas-phase mixing of the 13 C and 12 C regions is too slow to compete with the kinetics of carbon condensation.…”
Section: The Carbon-arc Synthesis: Determination Of Initial Reactantsmentioning
confidence: 99%
See 2 more Smart Citations
“…If, however, the dispersion of 13 C is nonstatistical, then the experiment is inconclusive. A nonstatistical result is interprétable as either a large-molecule formation mechanism or as an indicator that the gas-phase mixing of the 13 C and 12 C regions is too slow to compete with the kinetics of carbon condensation.…”
Section: The Carbon-arc Synthesis: Determination Of Initial Reactantsmentioning
confidence: 99%
“…These questions may be addressed through isotopic scrambling experiments. In these experiments, the starting material consists of regions of pure 13 C and regions of natural-abundance 13 C. If the isotopic distribution of a fullerene produced in this arc is statistical, and the 13 C atoms are randomly distributed throughout the CgQ framework, then most likely a small-molecule synthesis is occurring. If, however, the dispersion of 13 C is nonstatistical, then the experiment is inconclusive.…”
Section: The Carbon-arc Synthesis: Determination Of Initial Reactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more extensive ab initio calculations have been carried out by Jensen et al (1992). These authors also considered the intensities of the allowed v-i and 1/3 fundamental bands of 12 C3 and showed that their theoretical transition moments were in keeping with recent experimental observations (Schmuttenmaer et al 1990). …”
mentioning
confidence: 78%
“…Botschwina et al (2014) found a high degree of floppiness for l-C 3 H + but not as high as that of C 3 . In addition, Stein et al (2015) have recently computed that the lowest energy bending mode of l-C 3 H + lies at 125.7 cm −1 , which is about twice that of C 3 (∼63.4 cm −1 , Schmuttenmaer et al 1990). …”
mentioning
confidence: 99%